Language as a Medium of Palestinian Resistance: Metaphors of Resistance in the Poetry of Mahmoud Darwish - Nuh, Haqqul (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study examines language as a medium of resistance in the poems of Mahmoud Darwish. The purpose of this research is to identify the forms of resistance metaphors used in the poems and to analyze how these metaphors construct a discourse of resistance against colonial domination in Palestine. This research employs a descriptive qualitative approach using library research methods. The data consist of selected poems by Mahmoud Darwish that contain themes of homeland, identity, and the struggle of the Palestinian people. Data collection was carried out through close reading of the poems, followed by identifying and classifying metaphors related to resistance themes. The data were analyzed using semantic and discourse analysis approaches to reveal the meanings and functions of metaphors in constructing narratives of resistance. The findings indicate that metaphors such as land, home, roots, and identity function as linguistic symbols representing the suffering, struggle, and resistance of the Palestinian people. Therefore, Mahmoud Darwish’s poetry serves not only as an aesthetic literary expression but also as a discursive medium that strengthens collective identity and the discourse of resistance against colonialism.